Shared education in Northern Ireland: school collaboration in divided societies. (3rd May 2016) - Gallagher, Tony
Abstract: During the years of political violence in Northern Ireland many looked to schools to contribute to reconciliation. A variety of interventions were attempted throughout those years, but there was little evidence that any had produced systemic change. The peace process provided an opportunity for renewed efforts. This paper outlines the experience of a series of projects on 'shared education', or the establishment of collaborative networks of Protestant, Catholic and integrated schools in which teachers and pupils moved between schools to take classes and share experiences. The paper outlines the genesis of the idea and the research which helped inform the shape of the shared education project. The paper also outlines the corpus of research which has examined various aspects of shared education practice and lays out the emergent model which is helping to inform current government practice in Northern Ireland, and is being adopted in other jurisdictions. The paper concludes by looking at the prospects for real transformation of education in Northern Ireland.